ANALISIS PENGARUH TAX PLANNING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP FIRM VALUE MODEL RASIO TOBINS'Q DENGAN TRANSPARENCY SEBAGAI VARIABEL MODERASI - Wisti, Rizky Fitria; Ratnawati, Vince; Hanif, Rheny Afriana; Odiatma, Fajar (Jurnal Riset Akuntansi, 2021)
This study aims to analyze the effect of tax planning and CSR (corporate social responsibility) on company value. This study also aims to analyze the role of moderation of the transparency of the influence of tax planning and CSR on the value of financial service companies listed on the Indonesia Stock Exchange in 2014-2018. The dependent variable is measured using Tobins' Q. Data is obtained by using the method of collecting documentation data obtained from data tracking through electronic media such as annual report data and company financial statements that are sampled. The total sample in this study were 40 companies determined by the purposive sampling method. Data processing techniques in this study use the method of multiple linear analysis and Moderated Regression Analysis (MRA) with SPSS Version 25. The results of this study indicate that tax planning and CSR affect the value of the company. In addition, this study also found that transparency can moderate the effect of tax planning and CSR on corporate value.